Addressing the Risks That Trade Secret Protections Pose for Health and Rights - Allison Durkin; Patricia Anne Sta Maria; Brandon Willmore; Amy Kapczynski (Harvard FXB Center for Health and Human Rights, 2020)
Human rights frameworks afford everyone the right to health and the right to enjoy the benefits of scientific progress and its applications. Both come together to create state obligations to ensure access to medicines and other health technologies. Though the impact of patents on access to high-quality, affordable medicines and health technologies has been well described, there has been little attention to the impact of trade secrecy law in this context. In this paper, we describe how trade secrecy protection comes into conflict with access to medicines-for example, by preventing researchers from accessing clinical trial data, undermining the scale-up of manufacturing in pandemics, and deterring whistleblowers from reporting industry misconduct. The paper proposes measures to diminish the conflict between trade secrecy and health that are consistent with international law and will advance health without undermining innovation.